Prokrastinasi Akademik dan Niat Membeli Skripsi - Tondok, Marselius Sampe (ANIMA Indonesian Psychological Journal, 2008)
The aim of this research was to explore the correlation between the tendency of academic procrastination and the urge to buy a thesis. The population in this research were students taking the Research Proposal Construction item or being finishing their script. Subjects (N = 95) were students taken from the population through a stratified proportional random sampling. Data was compiled through an academic procrastination questionnaire and the urge to buy a thesis. The hypothesis was tested with Spearman’s Rank Order correlation. Result of the hypothesis testing reveals no correlation between academic procrastination and the urge to buy a thesis (rs = – 0.025; p = 0.811). Further analysis reveals that academic achievement is correlated with the urge to buy a thesis. Penelitian ini bertujuan untuk meneliti hubungan antara kecenderungan perilaku prokrastinasi akademik dengan niat untuk membeli skripsi.Populasi penelitian ini adalah mahasiswa yang sedang menempuh mata kuliah Penyusunan Proposal Penelitian atau sedang menyusun skripsi. Subyek penelitian(N=95) diambil dari populasi dengan teknik stratified proportional random sampling. Data diperoleh dengan menggunakan angket prokrastinasi akademik dan niat membeli skripsi. Hipotesis penelitian diuji dengan teknik korelasi Spearman’s Rank Order. Hasil uji hipotesis menunjukkan tidak ada hubungan antara prokrastinasi akademik dan niat membeli skripsi (rs=-0.25; p=0.811). Dari analisis lebih lanjut diketahui bahwa prestasi akademik berhubungan dengan niat membeli skripsi.